High-frequency mechanical energy harvester with direct current output from chemical potential difference - Li, Shaoxin (2022)
As an energy harvester that converts mechanical power into electrical energy, a triboelectric nanogenerator (TENG) with a pair of metallic and insulating electrodes can generate only the displacement current (Idis) in the electrodes, whereas a chemical potential difference generator (CPG) with a pair of semiconducting or/and metallic electrodes can generate both Idis and conduction current (Icon). Considering the effects of motion parameters on Idis and Icon is important for harvesting different mechanical energies in practical scenarios; the output characteristics of CPGs and traditional TENGs under different external resistance (R), contact-separation frequency (f), and maximum separation distance (xm) were systematically studied for the first time in this work. More interestingly, a direct current (DC) output can be generated directly by CPGs under R > 10 Mω or f > 100 Hz. This work not only provides a guideline for collecting different mechanical energies but also promotes the development of CPGs as an energy harvester and self-powered vibration sensor in the semiconductor industry.